COSSI, a cohort simulation model of forest growth and yield in the Solomon Islands - Burslam, D; Alder, D; Whitmore, T (Oxford Forestry Institute, University of Oxford, 1996)
A cohort simulation model of forest growth and yield in the Solomon Islands is presented. The model takes stand table information of the 12 common big tree species and simulates recruitment, growth and mortality of cohorts through time on the basis of basal area increment functions and size-specific mortality estimates derived over 1964-1994 from permanent sample plots in natural forest on Kolombangara, Solomon Islands. A cohort is defined as a set of trees on the same plot which are deemed sufficiently similar in size and condition to be grouped for the purpose of simulation. Recruitment is modelled in a two-step process involving the calculation of a total number of new recruits to be added to a plot, followed by partitioning this total according to species-specific probability values. Total recruitment and species-specific probability values are derived from empirical data on recruitment of the 12 species onto the Kolombangara plots following a cyclone in 1967. The model allows harvesting to be simulated according to user-defined logging rules and felling cycle. Post-logging mortality is predicted from functions relating mortality of residual stems on the Kolombangara plots to the degree of disturbance caused by the 1967 cyclone, and both harvesting intensity and post-logging mortality are extrapolated forward into the prediction of recruitment after lag periods of 7 and 10.5 years. The major limitation of the current model is that cohorts are updated according to parameters and functions obtained from plots in natural forest disturbed by a cyclone and not in managed forests disturbed by logging. Therefore we recommend that the model be used a tool for research and not as a guide to forest management. Future research should concentrate on developments of the framework model presented here, and collecting and analysing data from forests logged at known dates.